Zooplankton From a Reef System Under the Influence of the Amazon River Plume - Neumann-Leitão, Sigrid; Melo, Pedro A. M. C.; Schwamborn, Ralf; Diaz, Xiomara F. G.; Figueiredo, Lucas G. P.; Silva, Andrea P.; Campelo, Renata P. S.; Melo Júnior, Mauro de; Melo, Nuno F. A. C.; Costa, Alejandro E. S. F.; Araújo, Moacyr; Veleda, Dóris R. A.; et al. (Frontiers in Microbiology, 2018)
At the mouth of the Amazon River, a widespread carbonate ecosystem exists below the river plume, generating a hard-bottom reef (~9500 km2) that includes mainly large sponges but also rhodolith beds. The mesozooplankton associated with the pelagic realm over the reef formation was characterized, considering the estuarine plume and oceanic influence. Vertical hauls were carried out using a standard plankton net with 200 μm mesh size during September 2014. An indicator index was applied to express species importance as ecological indicators in community. Information on functional traits was gathered for the most abundant copepod species. Overall, 179 zooplankton taxa were recorded. Copepods were the richest (92 species), most diverse and most abundant group, whereas meroplankton were rare and less abundant. Species diversity (>3.0 bits.ind-1) and evenness (>0.6) were high, indicating a complex community. Small holoplanktonic species dominated the zooplankton, and the total density varied from 107.98 ind. m-3 over the reef area to 2,609.24 ind. m-3 in the estuarine plume, with a significant difference between coastal and oceanic areas. The most abundant copepods were the coastal species Oithona plumifera and Clausocalanus furcatus and early stages copepodites of Paracalanidae. The holoplanktonic Oikopleura, an important producer of mucous houses, was very abundant on the reefs. The indicator species index revealed three groups: 1) indicative of coastal waters under the influence of the estuarine plume (Euterpina acutifrons, Parvocalanus crassirostris, Oikopleura (Vexillaria) dioica and Hydromedusae); 2) characterized coastal and oceanic conditions (Clausocalanus); 3) characterized the reef system (O. plumifera). Two major copepods functional groups were identified and sorted according to their trophic strategy and coastal-oceanic distribution. The species that dominated the coastal area and the area over the rhodolith beds are indicators of the estuarine plume and are mixed with species of the North Brazil Current. These species practically disappear offshore, where occur oceanic species commonly found in other oligotrophic tropical areas. This ecosystem shows a mixture of estuarine, coastal and oceanic communities coexisting in the waters over the Amazon reefs, with no significant differences among these areas. However, the MDS clearly separated the communities along the salinity gradient in the plume.